2018
DOI: 10.1101/325126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theaflavins, polyphenols of black tea, inhibit entry of hepatitis C virus

Abstract: 20The treatment of hepatitis C virus (HCV) infection by combination of direct acting antivirals 21 (DAA), with different mode of action, has made substantial progress in the past few years. 22 3 47 development of HCV direct acting antivirals (DAA) like Daclatasvir, Sofosbuvir and Simeprevir, 48targeting viral proteins NS5A, NS5B polymerase or NS3/4A protease, respectively (5). These 49 approved DAA prominently increase the sustained viral response (SVR) up to ~95% in most 50 patients, depending primarily on di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…reported the antiviral property of polyphenolic compounds from black tea namely theaflavin, theaflavin-3′-monogallate, and theaflavin-3-3′-digallate during the early onset of hepatitis C viral infections under in-vitro conditions. Their study reported that theaflavin and its derivatives could inhibit viral replication and cell-to-cell proliferation (Chowdhury et al., 2018 ). They reported an EC 50 value of 17.89, 4.08, and 2.02 μM respectively had a significant impact against viral replication (Chowdhury et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…reported the antiviral property of polyphenolic compounds from black tea namely theaflavin, theaflavin-3′-monogallate, and theaflavin-3-3′-digallate during the early onset of hepatitis C viral infections under in-vitro conditions. Their study reported that theaflavin and its derivatives could inhibit viral replication and cell-to-cell proliferation (Chowdhury et al., 2018 ). They reported an EC 50 value of 17.89, 4.08, and 2.02 μM respectively had a significant impact against viral replication (Chowdhury et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Their study reported that theaflavin and its derivatives could inhibit viral replication and cell-to-cell proliferation (Chowdhury et al., 2018 ). They reported an EC 50 value of 17.89, 4.08, and 2.02 μM respectively had a significant impact against viral replication (Chowdhury et al., 2018 ). Chen et al.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds are well-known for their antioxidant, anti-inflammatory, and other disease-curing abilities [79]. Previously, theaflavins and its derivatives were reported for their effectiveness against Influenza [80], HSV-1 [81], hepatitis C virus [82], calicivirus [83] and HIV-1 [84]. Besides preventing inflammatory cytokine expression, theaflavins are effective in thwarting viral attachment/entry and replication [82,84].…”
Section: Anti-sars-cov Phytocompoundsmentioning
confidence: 99%
“…Previously, theaflavins and its derivatives were reported for their effectiveness against Influenza [80], HSV-1 [81], hepatitis C virus [82], calicivirus [83] and HIV-1 [84]. Besides preventing inflammatory cytokine expression, theaflavins are effective in thwarting viral attachment/entry and replication [82,84]. During the SARS outbreak in 2004, two theaflavin derivatives namely 3-isotheaflavin-3-gallate, theaflavin-3, 3′-digallate alongside tannic acid have been reportedas potential 3 CL Pro inhibitors with IC 50 values 7, 9.5 and 3 µM respectively [85].…”
Section: Anti-sars-cov Phytocompoundsmentioning
confidence: 99%